Ethnomedicinal study of Bryonia dioica, a plant used as anti-breast cancer herbal therapy in North West Algeria - Manager, Bachir Benarba (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Bryonia dioica (Cucurbitaceae), a climbing perennial herb, is widely used in traditional medicine in Algeria. The present study aimed to record the ethnomedicinal uses of the plant in North West Algeria. Our results showed that B. dioica is widely used to treat several ailments such as cancer (26%), hypercholesterolemia (22%), and diabetes (18%). B. dioica roots are taken orally, alone or mixed with different ingredients of non-plant origin such as water or honey. Breast cancer was the most frequent disease reported to be treated with B. dioica. These findings suggest that B. dioica could be considered as a promising source for developing novel therapeutics against breast cancer.